Development and Validation of an Interprofessional Collaboration Scale for Home Health Care for the Frail Elderly - Keiko Tsukasaki; Kaoru Kyota; Tomoya Itatani (Elsevier, 2022)
S U M M A R Y: Purpose: The purpose of this study was to develop an interprofessional collaboration (IPC) scale for home health care for frail elderly. Methods: The first items of the IPC scale included collaboration members' attitudes, awareness, motivation, team strength, communication, relationships, information, care recipients' interests, effects, development, utilization of social resources, contributions to the community, and crisis management. The subjects were 512 care managers who work in home care support offices across Japan. They manage interprofessional collaboration in home health care for frail elderly who need care at 65 years old and above. The scale's construct validity, internal consistency, the validity of known groups, concurrent validity, and test-retest reliability (193 subjects) were examined. Results: The final IPC scale's items consisted of four factors (37 items): the strength of interprofessional teams (16), the management of collaborative systems (7), effects of collaboration (8), and communication (6). Four factors explained 58.6% of the total explained variance. The modified model fit of the scale achieved acceptable levels. The Cronbach's α coefficient for all items was .97. The sum of communication factor in the cities/wards group was lower than those in the towns/villages group. There were differences between the sum and each factor with different levels of ease to collaborate. The intraclass correlation coefficient for all items in the first and second assessments was .875. Conclusions: The validity and reliability of the IPC scale have been verified. This scale can be used to assess the IPC for home health care for frail elderly.